Virological surveillance of SARS-CoV-2 in an Italian northern area: comparison of Real Time RT PCR cycle threshold (Ct) values in three epidemic periods - Veronesi, Licia; Colucci, Maria Eugenia; Pasquarella, Cesira; Caruso, Luca; Mohieldin Mahgoub Ibrahim, Mostafa; Zoni, Roberta; Pergreffi, Massimiliano; Arcuri, Carlo; Seidenari, Chiara; Viani, Isabella; Capobianco, Emanuela; Mezzetta, Sandra; et al. (Acta Biomedica Atenei Parmensis, 2020)
Aim of the study was to investigate the differences in Ct values in nasopharingeal swabs collected in three SARS-CoV-2 epidemic periods: first one from February 23 to March 25 (14 days from lockdown started on March 11); the second one from March 26 to May 18 (14 days from the end of strict lockdown on May 4) and the third one from May 19 until June 15. Viral RNA was detected in nasopharyngeal swabs obtained both from inpatients and outpatients. COVID-19 infection was confirmed according to the Ct values for N1 and N2 genes ascertained by Real-Time RT-PCR assay as described by the CDC. We calculated the prevalence of nasopharyngeal swabs tested positive for SARS-CoV-2, the mean and median of the Cts and the percentage of samples equal or below the Ct value of 25 in the 3 periods considered. The average value of Ct increased, going from 24.80 in the first epidemic period to 26.64 in the second period to 28.50 in the third period (p <0.001). The percentage of samples with Ct lower than or equal to 25 also decreased sharply from 54.7% to 20.0%. These findings need to be integrated with epidemiological and clinical data.